Subclinical herpesvirus shedding among HIV-1-infected men on antiretroviral therapy. (24th September 2017) - Agudelo-Hernandez, Arcadio; Chen, Yue; Bullotta, Arlene; Buchanan, William G.; Klamar-Blain, Cynthia R.; Borowski, Luann; Riddler, Sharon A.; Rinaldo, Charles R.; Macatangay, Bernard J.C.
Abstract : Objective: We evaluated the subclinical shedding of six different herpesviruses in antiretroviral drug-treated HIV-positive [HIV(+)] MSM, and determined how this is associated with markers of inflammation and immune activation. Methods: We obtained blood, semen, throat washing, urine, and stool from 15 antiretroviral-treated HIV-1-infected MSM with CD4 + T-cell reconstitution, and 12 age-matched HIV-negative [HIV (−)] MSM from the Multicenter AIDS Cohort Study at four timepoints over 24 weeks to measure DNA levels of cytomegalovirus (CMV), Epstein–Barr virus (EBV), herpes simplex virus 1 and 2, human herpesvirus 6 (HHV6), and HHV8. T-cell activation and plasma levels of soluble markers of inflammation and activation were also measured at the corresponding timepoints. Results: HIV(+) participants had a trend for higher total herpesvirus shedding rate. HIV(+) participants also had a significantly higher rate of shedding EBV and CMV compared with the HIV(−) group. Herpesvirus shedding was mostly seen in throat washings. In the HIV(+) group, herpesvirus shedding rate inversely correlated with plasma levels of interferon γ-induced protein 10 and soluble CD163. CMV DNA levels negatively correlated with levels of T-cell activation. There was a trend for a positive correlation between EBV shedding rate and plasma soluble CD14. HHV6 shedding rate negatively correlated with plasma levels of interleukin-6, soluble CD163, and interferon gamma-induced protein 10. Correlations were not observed among HIV(−) individuals. Conclusion: Among treated HIV-infected MSM, there are higher subclinical shedding rates of some herpesviruses that occur in different body compartments and negatively correlate with levels of inflammation and immune activation. Abstract : Supplemental Digital Content is available in the text